Prognostic Value of Ki-67 Index, Cytology, and Growth Pattern in Mantle-Cell Lymphoma: Results From Randomized Trials of the European Mantle Cell Lymphoma Network - Hoster, Eva; Rosenwald, Andreas; Berger, Françoise; Bernd, Heinz-Wolfram; Hartmann, Sylvia; Loddenkemper, Christoph; Barth, Thomas F E; Brousse, Nicole; Pileri, Stefano; Rymkiewicz, Grzegorz; Kodet, Roman; Stilgenbauer, Stephan; et al. (Journal of clinical oncology, 2016)
PURPOSE: Mantle-cell lymphoma (MCL) is a rather aggressive B-cell malignancy whose considerable variability of individual outcome is associated with clinical characteristics (Mantle Cell Lymphoma International Prognostic Index [MIPI]). The Ki-67 index is a strong independent prognostic factor; however, the biologic MIPI (MIPI-b) distinguishes only two groups, which does not appropriately depict the clinical heterogeneity. By using the cohort from the European MCL Younger and MCL Elderly trials, we aimed to evaluate the additional prognostic impact of cytology and growth pattern and to improve risk stratification with the Ki-67 index and MIPI. PATIENTS AND METHODS: Diagnostic tumor biopsies were reviewed by the European Mantle Cell Lymphoma Pathology Panel to determine Ki-67 index by using published guidelines, cytology, and growth pattern. We evaluated prognostic effects for overall survival (OS) by Cox regression. For the cohort used for MIPI-b development (German Low-Grade Lymphoma Study Group [GLSG] 1996 and GLSG2000), we checked whether the equally weighted combination of Ki-67 index (dichotomized at the validated 30% cutoff) and MIPI risk groups was adequate and compared the prognostic power of this modified combination to MIPI and MIPI-b for the MCL Younger/MCL Elderly cohort. RESULTS: The Ki-67 index was assessed in 508 of 832 patients (median age, 62 years). Blastoid cytology was associated with inferior OS independently of MIPI but not independently of the Ki-67 index. Growth pattern was not independently prognostic. The modified combination of the Ki-67 index and MIPI separated four groups with 5-year OS: 85%, 72%, 43%, and 17% (P < .001) and was more discriminative than MIPI and MIPI-b. CONCLUSION: Using the Ki-67 index is superior to using cytology and growth pattern as prognostic factors in MCL. The modified combination of the Ki-67 index and MIPI showed a refined risk stratification, reflecting their strong complementary prognostic effects while integrating the most relevant prognostic factors available in clinical routine.
Keywords: antigen Ki-67; proporcionální rizikové modely; hodnocení rizik; Lymphoma, Mantle-Cell; Male; retrospektivní studie; Risk Assessment; Risk Factors; Cell Proliferation; prognóza; lymfom z plášťových buněk; Kaplan-Meier Estimate; Proportional Hazards Models; randomizované kontrolované studie jako téma; Europe; Adult; biopsie; Kaplanův-Meierův odhad; Aged; dospělí; imunohistochemie; mužské pohlaví; senioři; Tumor Burden; diskriminační analýza; Evropa; Multivariate Analysis; Time Factors; senioři nad 80 let; lidé; ženské pohlaví; Immunohistochemistry; Discriminant Analysis; Ki-67 Antigen; Humans; Randomized Controlled Trials as Topic; časové faktory; rizikové faktory; Aged, 80 and over; prediktivní hodnota testů; proliferace buněk; tumor burden; Prognosis; Biopsy; Retrospective Studies; multivariační analýza; Female; lidé středního věku; Predictive Value of Tests; Middle Aged